The pull of Carabao Island: Investigating local tourists’ revisit intentions as basis for tourism and hospitality development - Turner Evon F. de Torres; Joanamae P. Juaneza; Krisha Klaire M. Vergara; Christine Gail S. Bacani; Joyce M. Fajiculay; Raymund Jashua F. Galang; Gesan P. Molina (Bahasa Indonesia, 2026)
This quantitative study investigates factors influencing local tourists' revisit intentions to Carabao Island. Integrating the Theory of Planned Behavior with Customer Satisfaction and Loyalty frameworks, the research analyzed the interplay of perceived risk, satisfaction, and experience among 162 Filipino tourists. Findings identify Tourist Experience (Weighted Mean = 4.44) and Tourist Satisfaction (WM = 4.43) as the primary drivers for returning, both receiving "Strongly Agree" ratings. Specifically, 64.8% of respondents were "Very Satisfied" with attractions, while 62.3% felt the same regarding accommodation. The island’s pleasant atmosphere emerged as a top experiential factor (WM = 4.55). Conversely, Perceived Risk exerted the least influence (WM = 3.73). While tourists generally feel transportation is safe (WM = 3.94), statistical analysis reveals that risk sensitivity varies significantly by age and income. Younger travelers and those in lower-income brackets (PHP 15,000–20,000) show higher sensitivity to risks. The study concludes that Carabao Island successfully delivers memorable experiences. Recommendations include maintaining service quality and tailoring marketing to address the specific risk concerns of younger, lower-income demographic segments to ensure long-term viability.